Is business school best for you? [electrical engineering careers]. - Karlin, S.
While business school is still not the most common path for electrical engineers, the popularity of MBAs as conduits to higher salaries, faster promotions, and greater management and marketing skills has been. In this paper, the author details some points to ponder if you're mulling an MBA
Keywords: MBA; Business school; Electrical engineering education; Engineering careers; Management skills; Marketing skills; Promotions; Salaries